Exploration of experimental design and statistical methods using the stick‐on‐the‐wall spaghetti rule. (11th January 2018) - Montangero, Simone; Vittone, Francesca; Olderbak, Sally; Wilhelm, Oliver
Summary: We present a versatile scenario to introduce students to statistics: the test that spaghetti sticks only if sufficiently done. The statistical analyses can be performed at different levels of complexity and formal correctness, adapting it to the students' age.